Implementasi Metode VIKOR - AHP Dalam Perekrutan Jurnalis pada Kantor Sumut Pos - Sweety, Miana; Irawan, Muhammad Dedi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Sumut Pos is a company operating in the oldest print media sector with the largest number one circulation published in Medan. The selection stage for recruiting journalists takes a lot of time so the decision-making process takes a long time. The aim of this research is to build a decision support system to make it easier for editorial heads to determine prospective journalists according to their expectations and reduce the time required for the recruitment process. This research uses the AHP and VIKOR (ViseKriterijumska OPT.imizacija I Kompromisno Resenje). methods. There are stages of observation research, literature study interviews, questionnaires, problem identification, system design and implementation. The findings of this study provide editorial administrators with a decision support tool to help with the hiring process